In situ unravelling surface plasmon resonance subject-object role of BiVO4@Ag in photocatalytic water splitting - Ding, Guodao; Zhang, Yanyang; Zhang, Yinjun; Gu, Jiajun; Hong, Dapeng; Li, Bo; Zhang, Jiawei; Zhu, Guoliang; Chen, Guangri; Shan, Lianwei; Wu, Haitao; Xu, Huanyan; et al. (Journal of colloid and interface science, 2026)
Surface plasmon resonance (SPR) of noble metal particles has been recognized to play a significant role in photocatalysis. We designed the BiVO4@Ag system by photo-deposition to prove the special role of Ag nanoparticles (NPs) in promoting water splitting. The BiVO4@Ag considerably increases light absorption by the SPR effect of Ag NPs. A strong interface effect in BiVO4@Ag-5 is effectively demonstrated through in situ vibration frequency variation of VO bonds from 826.1 cm−1 to 820.9 cm−1. Loaded Ag NPs in BiVO4 improve slightly the hot electron lifetime (1.80 fs) compared with BiVO4 (1.53 fs). Ag NPs significantly raise the conduction band potential of BiVO4@Ag system and evidently enhance the electrochemical specific surface area. The BiVO4@Ag also exhibits significant thermal effects when illuminated with a light source (>520 nm). However, BiVO4@Ag does not exhibit photocatalytic hydrogen evolution ability as using above light source, indicating that the pyroelectric current does not directly promote the photocatalytic hydrogen evolution performance of BiVO4@Ag. Using a light source (<520 nm) to excite and filter out the photothermal effect of BiVO4@Ag-5, an obvious reduction of hydrogen evolution (from 72.1 μmol to 18.3 μmol) can happen. The excited SPR effect with a light source (>520 nm, filter out the intrinsic absorption of BiVO4 matrix) proves that the SPR effect can only accelerate the hydrogen evolution rate of the system. The increase in temperature cannot significantly improve the photocatalytic hydrogen evolution rate of BiVO4@Ag-5. Ab initio molecular dynamics calculations based on solvation models suggest that the surface of BiVO4 mainly provides the role of water decomposition, while Ag NPs mainly provide the role of photocatalytic hydrogen evolution. These findings provide a unique perspective to understand the photocatalytic water splitting behaviors, which are of general significance in various energy conversion reactions. [Display omitted] •Ag NPs significantly raise the conduction band potential of BiVO₄@Ag system and optimize electron transfer dynamics.•The VO bonds elongation is beneficial for the formation of effective electronic transmission channels.•HER of BiVO₄@Ag is only activated by intrinsic absorption due to SPR effect does not directly contribute to HER.•BiVO₄ surfaces primarily drive water dissociation, while Ag NPs enhance hydrogen migration and evolution kinetics.